The ERBB2 Exonic Variant Pro1170Ala Modulates Mitogen-Activated Protein Kinase Signaling Cascades and Associates with Allergic Asthma - Sio, Yang Yie; Gan, Wei Liang; Ng, Wing Shan; Matta, Sri Anusha; Say, Yee How*; Teh, Keng Foo *; Wong, Yi Ru *; Smyrna Moti, Rawanan Shah *; Kavita, Reginald *; Chew, Fook Tim (Karger Publishers, 2023)
Introduction: Previous studies have indicated the ERBB2 genetic variants in the 17q12 locus might be associated with asthma; however, the functional effects of these variants on asthma risk remain inconclusive. This study aimed to characterize the functional roles of asthma-associated ERBB2 single nucleotide polymorphisms (SNPs) in asthma pathogenesis by performing genetic association and functional analysis studies.